Existence, Uniqueness and Blow-up Rate of Large Solutions of Quasi-linear Elliptic Equations with Higher Order and Large Perturbation (Journal of Partial Differential Equations, 2013)
We establish the existence, uniqueness and the blow-up rate of the large positive solution of the quasi-linear elliptic problem $$-\triangle_{p}u=λ (x)u^{θ -1}-b(x)h(u), in Ω, $$ with boundary condition $u=+∞ $ on $\partial Ω $, where $Ω \subset R^N$ $(N≥ 2)$ is a smooth bounded domain, $1